2011
DOI: 10.5402/2011/238360
|View full text |Cite
|
Sign up to set email alerts
|

Thoracopagus Conjoined Twins: A Case Report

Abstract: Objective. Conjoined twin is a rarely seen congenital anomaly together with severe mortality and morbidity. The more common types of conjoined twins include the thoracopagus type, where the fusion is anterior, at the chest, and involves the heart. We are reporting one case of conjoined thoracopagus twins diagnosed by ultrasonography at 11 weeks. Case Report. In a multigravid pregnant woman who has been admitted to our clinic with a diagnosis of conjoined twins, thoracopagus, by ultrasonography at an 11-week ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 9 publications
0
24
0
2
Order By: Relevance
“…Only one type of twin mentioned in the third type with lateral fusion is Parapagus (fused by side). 9 In one of the case series of 74 cases of conjoined reported by Chih-Ping Chen et al the incidence of parapagus conjoined twins was found to be 13.5% establishing the rarity of this condition. 4 The prognosis of conjoined twins is poor.…”
Section: Discussionmentioning
confidence: 96%
“…Only one type of twin mentioned in the third type with lateral fusion is Parapagus (fused by side). 9 In one of the case series of 74 cases of conjoined reported by Chih-Ping Chen et al the incidence of parapagus conjoined twins was found to be 13.5% establishing the rarity of this condition. 4 The prognosis of conjoined twins is poor.…”
Section: Discussionmentioning
confidence: 96%
“…Conjoined twins are always joined at homologous sites and the clinical classification is based on the most prominent site of union, combined with the suffix 'pagus' such as thoracopagus (chest), omphalopagus (umbilicus), ischiopagus (hip), pygopagus (rump), rachipagus (spine), craniopagus (cranium), cephalopagus (head), and parapagus (side) [3] (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The older and traditional theory is fission, in which the fertilized egg splits partially and conjoined twins represent delayed separation of the embryonic mass after 12th day of fertilization. The second theory is fusion, in which a fertilized egg completely separates, but stem cells find alike stem cells on the other twin and fuse the twins together [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…1 Conjoined twins are a subset of monozygotic twins in which incomplete embryonic division occurs on 13 to 15th days following conception resulting in varying degrees of fusion between the two foetuses. 2 Conjoined twinning is rare, occurring in about 1% of monochorionic twins with an estimated incidence ranging from 1:30,000 to 1:2,00,000 live births and 1 in 650 to 900 twin deliveries.…”
Section: Introductionmentioning
confidence: 99%